2019
DOI: 10.1016/j.heliyon.2019.e02825
|View full text |Cite
|
Sign up to set email alerts
|

Detailed quantum mechanical, molecular docking, QSAR prediction, photovoltaic light harvesting efficiency analysis of benzil and its halogenated analogues

Abstract: The structural, spectroscopic various physico-chemical and biological characteristics of the organic molecule benzil (BZL) and derivatives, 1,2-bis(4-methylphneyl)-1,2-ethanedione (DMB), 4,4′-difluorobenzil (DFB), 4,4′-dichlorobenzil (DCB) and 4,4′-dibromobenzil (DBB) have been studied by various computational methods. The experimental and scaled simulated Raman and IR spectra were compared and found close agreement. Assignments of important peaks are also presented. Detailed information pertaining to the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 54 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…In this context, molecular docking studies become crucial as they provide an opportunity to gain information about ligand-receptor interaction before any experimental drug test. It can be found out which region of the protein the ligand binds to, what kind of interactions it makes, and their binding energies in these docking calculations [ 71 , 72 ]. The molecular docking calculations of various furopyrimidine compounds have shown that they behave as an inhibitor of EGFR tyrosine kinase [ [17] , [18] , [19] , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, molecular docking studies become crucial as they provide an opportunity to gain information about ligand-receptor interaction before any experimental drug test. It can be found out which region of the protein the ligand binds to, what kind of interactions it makes, and their binding energies in these docking calculations [ 71 , 72 ]. The molecular docking calculations of various furopyrimidine compounds have shown that they behave as an inhibitor of EGFR tyrosine kinase [ [17] , [18] , [19] , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the first transition, f was 0.58, which implies that the molecule possessed good light-harvesting efficiency (LHE) that is expressed as a function of f , as follows: LHE = 1–10 −f [ 36 , [45] , [46] , [47] , [48] , [49] , [50] ]. The value was 0.7376 for the first transition, which indicated that the compound could absorb 73.76% of incident-light energy for electronic excitation at that wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Biological activities were collected from PASS online [ 52 , 53 , 54 ], and corresponding protein activities were downloaded from the RCSB site [ 55 ] for protein data bank IDs: 1DB4 and 2PWB are macromolecules for human non-pancreatic secretory phospholipase A2 (hnps-PLA2 and protease K. The molecular docking analysis work was performed by using AutoDock Vina [ 56 ], Bio Discovery Studio, and package software [ 57 ]. We repeated the docking simulation multiple times to check whether the ligand binds to the same binding site, and in all cases, we found that the same binding site is preferred.…”
Section: Methodsmentioning
confidence: 99%